2019
DOI: 10.1177/0021909619867110
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Gender-based Violence and Harmful Traditional Practices against Women in the Tigray Region, Ethiopia

Abstract: In Ethiopia, large numbers of women are at higher risk of gender-based violence and harmful traditional practices. The main aim of the study is to explore the prevalence rate of gender-based violence and harmful traditional practices against women in the Tigray region, Ethiopia. In this study, a total of 1253 women were surveyed, of which 560 were from rural areas. Further, 14 focus group discussions and in-depth key informant interviews were conducted with relevant governmental and non-governmental bodies. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Evidence is needed to understand how best to meet their health-care needs and to shape culturally appropriate. Also agree with Gebre et al [24] who found that female genital mutilation is a traditional harmful practice that violates the rights and dignity of women and girls. Regarding to nursing student's knowledge about woman right to health the present study shows that majority of studied sample had incorrect knowledge during preintervention and had improvement of knowledge in immediate post intervention and 8 weeks post intervention.…”
Section: Regarding To Sociodemographic Characteristics Of Adolescentsupporting
confidence: 89%
“…Evidence is needed to understand how best to meet their health-care needs and to shape culturally appropriate. Also agree with Gebre et al [24] who found that female genital mutilation is a traditional harmful practice that violates the rights and dignity of women and girls. Regarding to nursing student's knowledge about woman right to health the present study shows that majority of studied sample had incorrect knowledge during preintervention and had improvement of knowledge in immediate post intervention and 8 weeks post intervention.…”
Section: Regarding To Sociodemographic Characteristics Of Adolescentsupporting
confidence: 89%
“…Further, although the AGYW interviewed in this study had good knowledge about what constitutes GBV; there was often acceptance of GBV, likely perpetuated by cultural norms and gender roles which need to be addressed to increase uptake and continuation of GBV health services. According to United Nations Economic Commission for Africa and the African Centre for Gender and Social Development (2010), there are numerous reasons why GBV may be accepted by young women including the predominance of a patriarchal system, acceptance of GBV as a cultural norm or stigma attached to being a female victim of violence [38]. Interestingly, some cultural and social norms may perpetrate specific forms of violence.…”
Section: Knowledge Of Gbv Among Agywmentioning
confidence: 99%
“…The effects of SGBV can include depression, poor reproductive health outcomes, alcohol and substance use, and even death [ 4 , 7 , 8 ]. Besides having personal effects on survivors, SGBV can have serious consequences for a country’s economy.…”
Section: Introductionmentioning
confidence: 99%